Quality of Life is Diminished in Patients with Tetralogy of Fallot with Mild Residual Disease: A Comparison of Tetralogy of Fallot and Isolated Valvar Pulmonary Stenosis - Bhatt, Shivani M. (Pediatr Cardiol, 2017)
The objective of this study is to compare quality of life (QOL) in patients with mild pulmonary insufficiency (PI) after Tetralogy of Fallot (TOF) repair or after balloon dilation for isolated valvar pulmonary stenosis (VPS). A cross-sectional study of patients with TOF (n = 12) and VPS (n = 19), ages 8–18 years, who underwent cardiac magnetic resonance (CMR) and cardiopulmonary exercise test (CPET) was conducted. Patients with genetic syndromes were excluded. The groups were matched by severity and duration of PI using propensity scores. PI was greater than mild if the regurgitant fraction by CMR was >20%. Health status and QOL assessment included Child Health Questionnaire Child Self-Report (CHQ-CF87), Child Health Questionnaire Parent Report (CHQ-PF50), and Pediatric Cardiac QOL Instrument (parent and patient). QOL scores were compared between groups. Due to propensity matching, the groups had, at worst, mild PI and normal right ventricular ejection fraction on CMR. Parental perception of QOL was significantly worse in TOF as compared to VPS in the domains of general perception of health (P = 0.03), physical functioning (PF; P = 0.004), and family cohesion (P = 0.048). There were no differences in self-reported QOL between groups. There was no association between QOL and right ventricular function on CMR or percent-predicted maximal oxygen consumption on CPET in both groups. Parent-perceived QOL, in the domains of general health perception, PF, and family cohesion, is significantly reduced in patients with TOF with mild residual disease suggesting that the psychosocial impact of congenital heart disease may be significant even with successful repair and satisfactory medical status.